Among the Trees. - Rugoff, Ralph; Hayward Gallery, London; Kastner, Jeffrey; Pasquinelli, Matteo (Londen : Hayward Gallery, 2020)
Adams, Robert ; Ahtila, Eija-Liisa ; Barrada, Yto ; Calle, Johanna ; Carnegie, Gillian ; Dean, tacita ; Doig, peter ; Durham, Jimmie ; Everberg, Kirsten ; Gallaccio, Anya ; Gill, Simryn ; Graham, Rodney ; Guowei, Shi ; Hayden, Hugh ; Jospin, Eva ; Kadonaga, kazuo ; Kentridge, William ; Khedoori, Toba ; Lambri, Luisa ; Ho Lee, Myoung ; Leonard, Zoe ; Longo, Robert ; Mann, Sally ; McQueen, Steve ; Neudecker, Mariele ; Overton, Virginia ; Paine, Roxy ; Penone, Guiseppe ; Rodriguez, Abel ; Rondinone, Ugo ; Shaw, George ; Smithson, Robert ; Steinkamp, Jennifer ; Struth, Thomas ; Sussman, Rachel ; Marthine Tayou, Pascale ; Wall, Jeff
Among the Trees, Hayward Gallery, London, 4 March - 17 May 2020
boek